Alkali Activated Fly Ash Blast Furnace Slag Composites - Ghosh, Kushal; Ghosh, Partha (Boca Raton : CRC Press, 2020)
This book covers relevant synthesizing parameters, their interactions, and advantages of blending fly ash and blast furnace slag as source material, their relationship with mechanical properties and microstructure including guidelines to produce an optimal mix proportion. Further, it discusses related durability aspects, mechanical properties and reaction products and their inter-relationship. It explains phase characterization with XRD/SEM, change in the bond formulations with FTIR, FESEM and EDAX analysis. A mix design guideline based on empirical statistical concept has been put forward for professionals to manufacture customized activated fly ash composites in presence of slag. Aimed at graduate/senior undergraduate students, researchers in civil engineering, construction engineering, ceramics, material sciences, this book: Covers mechanical and microstructural properties, curing, durability of blended Alkali- activated composites with fly ash and blast furnace slag. Proposes a guideline for mix design on chemical compositions of ingredients, relationship of synthesizing parameters, workability, target strength. Describes sustainable green material manufacturing methodologies. Discusses issues like microstructural properties and reaction mechanism. Explores related modern experimental techniques like XRD, FTIR, MIP and so forth.
OCLC-licensed vendor bibliographic record.
Keywords: Fly ash; Composite materials; TECHNOLOGY / Engineering / Civil; TECHNOLOGY / Material Science